A current mirror for low voltage, high performance analog circuits - Rajput, S.S.; Jamuar, S.S. (Springer, 2003)
A current mirror for low voltage analog and mixed mode circuits is proposed. The current mirror has high input and output voltage swing capability and can operate at ±1.0 V supply. P-Spice simulations confirm the input current range of 1 μA to 500 μA with 2.5 GHz bandwidth for the proposed current mirror. Adaptive biasing increases the input voltage swing capability and decreases the undesired offset current. Resistive and capacitive compensation are used to increase its bandwidth.